2019
DOI: 10.12691/ajmcr-7-12-9
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor and Statin Interaction Induces Rhabdomyolysis and Acute Renal Failure: Case reports and Scoping Review

Abstract: Ever since evidence about the increased risk of stent thrombosis with drug eluting stents (DES) surfaced in 2005, the Food and Drug Administration (FDA) has recommended the use of dual antiplatelet therapy (aspirin with P2Y12 inhibitor) following DES placement. The PLATO trial demonstrated lower mortality rates with the use of Ticagrelor when compared to clopidogrel (9.8% vs. 11.7%, p<0.001) when treating patients with acute coronary syndrome. Given their pleiotropic benefits, statins are today the second most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…19 A review of the literature revealed that rosuvastatin was the most common statin used with ticagrelor in patients who developed rhabdomyolysis. 20 It also showed that most statins were being taken at a high-intensity dose (such as rosuvastatin 20 or 40 mg), which is similar to this case in which Ms. Y was taking rosuvastatin at the high-intensity dose of 20 mg orally daily. Unlike this case, the vast majority of patients in the literature were taking an ACE inhibitor or an ARB, while Ms. Y was not.…”
Section: ■ Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…19 A review of the literature revealed that rosuvastatin was the most common statin used with ticagrelor in patients who developed rhabdomyolysis. 20 It also showed that most statins were being taken at a high-intensity dose (such as rosuvastatin 20 or 40 mg), which is similar to this case in which Ms. Y was taking rosuvastatin at the high-intensity dose of 20 mg orally daily. Unlike this case, the vast majority of patients in the literature were taking an ACE inhibitor or an ARB, while Ms. Y was not.…”
Section: ■ Discussionsupporting
confidence: 62%
“…The case was also different in that the time from initiation of ticagrelor and a statin to the development of rhabdomyolysis was approximately 4 months, whereas previous cases reported onsets of around a few weeks to 2 months. 20 This delayed onset of rhabdomyolysis and acute renal failure is a unique aspect of this case that may be explained by the absence of an ACE inhibitor or ARB, which potentially caused less decline in renal function, and therefore, less impairment of rosuvastatin elimination.…”
Section: ■ Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The interaction between rosuvastatin and ticagrelor, in particular, has not received due attention. Despite a recent literature review revealing 11 cases of a major DDI between statins and ticagrelor resulting in rhabdomyolysis and renal failure, with rosuvastatin being the most commonly used statin, 5 the 2016 Scientific Statement from the American Heart Association (AHA) ("Recommendations for Management of Clinically Significant Drug-Drug Interactions with Statins and Select Agents Used in Patients with Cardiovascular Disease") still did not list this interaction among the 49 listed. 6 Additionally, there are no dose adjustment recommendations for those on ticagrelor and rosuvastatin, and both the Food and Drug Administration (FDA) package inserts and Summary of Product Characteristics (SmPC) are without interactions or warnings.…”
Section: Introductionmentioning
confidence: 99%